Pengaruh Loyalitas dan Disiplin Kerja Terhadap Kinerja Pegawai (Studi Pada Perusahaan Umum Daerah Sumber Sejahtera di Bangkalan) - Nusantara, Muhammad Adil Hakim; wispandono, Raden Mas Mochammad (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
An organization cannot survive and run without employees or human resources. This study employed a quantitative approach with a cluster sampling technique with a total of 136 respondents. The data collection procedure employed a questionnaire with analysis techniques using multiple linear regression analysis methods. The results showed that (1) the work loyalty variable had a positive effect on employee performance with a t-count of 4.811 table of 1.978 with a significant level of 0.000 0.05, (2) work discipline had a positive effect onemployee performance with a t-count of 5.649 t-table of 1.978 with a significant level of 0.0000.05, (3) loyalty and work discipline simultaneously had a significant effect on employee performance with an F- count value of 99.321 F-table 3.06 with a significance level of 0.0000.05, (4) work discipline had a dominant effect on employee performance with a beta value of 0.510 with a significance level of 0.000 0.05.